2017
DOI: 10.4172/2155-6105.s11-016
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana’s Role in The Adolescent Population

Abstract: Marijuana is the most commonly used illicit substance in the United States and worldwide. The smoking of marijuana is an increasingly observed phenomenon in the adolescent population and even more common nowadays than cigarette smoking. A special focus should therefore aim to the effects of marijuana in that particular age group.Adolescents are particularly vulnerable to the effects of marijuana because their brain and neuro-circuits are still developing. The exposure of marijuana to the still pruning brain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The article by Miller et al [6] also discussed on marijuana as a schedule I controlled substance and highlighted its necessity to come under 'medical marijuana' law. However, another article justified the necessary use of marijuana in adolescents [7]. In the article by Yankey et al [8], recreational use of marijuana has been suggested to be associated with cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article by Miller et al [6] also discussed on marijuana as a schedule I controlled substance and highlighted its necessity to come under 'medical marijuana' law. However, another article justified the necessary use of marijuana in adolescents [7]. In the article by Yankey et al [8], recreational use of marijuana has been suggested to be associated with cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a strong association between the onsets of other psychiatric disorders, in context with the use of marijuana. This article presented by Oberbarnscheidt et al [7], is a review of the current scientific literature with the aim to focus on the indications, outcomes, toxic effects and pathological evidence from the use of marijuana in the adolescents.…”
Section: Introductionmentioning
confidence: 99%